Optimization of Diagnostic Criteria in Patients with Vertigo - Nasretdinova M. T.; Normuradov N. A.; Nu'monov A. I. (Journal of Science in Medicine and Life, 2025)
Dizziness is frequent reason of address to the neurologist. The study of principal reasons of dizziness became a research aim for patients. 75 patients appealings to the neurologist and otorhinolaryngologist in connection with complaints about dizziness of system character are inspected. The stated below clinical inspections allow to educe the most widespread reasons of system dizziness and in good time to suspect the critical for life of patient damages of central departments of vestibular analyzer.